Moral judgment as information processing: an integrative review - Guglielmo, Steve (Frontiers in Psychology, 2015)
This article reviews dominant models of moral judgment, organizing them within an overarching framework of information processing. This framework poses two fundamental questions: (1) What input information guides moral judgments?; and (2) What psychological processes generate these judgments? Information Models address the first question, identifying critical information elements (including causality, intentionality, and mental states) that shape moral judgments. A subclass of Biased Information Models holds that perceptions of these information elements are themselves driven by prior moral judgments. Processing Models address the second question, and existing models have focused on the relative contribution of intuitive versus deliberative processes. This review organizes existing moral judgment models within this framework, critically evaluates them on empirical and theoretical grounds, outlines a general integrative model grounded in information processing, and offers conceptual and methodological suggestions for future research. The information processing perspective provides a useful theoretical framework for organizing extant and future work in the rapidly growing field of moral judgment.